Peran Mediasi Komitmen Organisasi Pada Pengaruh Stres Kerja Dan Persepsi Dukungan Organisasi Terhadap Intensi Keluar Karyawan (Studi Empiris Pada Perusahaan Pembiayaan di Kota Makassar) - Wahdaniah Wahdaniah; Heru Kurnianto Tjahjono; Tri Maryati (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2016)
The purpose of this research is to investigate the influence of job stress an perceived organizational support on turnover intention with organizational commitment  being intervening variable.The study was conducted at the finance company in Makassar, the population in this study is marketing employees who work in finance companies in Makassar. Respondents who give an answer to this study as many 172 employees. Data is processed using Structural Equation Modeling (SEM) which assisted by application program of Analysis of Moment Structure (AMOS) version 21.0. The analysis showed five accepted hypothesis, there is a negative and significant influence between komitmen organisasi  to turnover intention, there is a negative and significant influence between job stress and komitmen organisasi , there is a positive and significant influence between persepsi dukungan organisasito komitmen organisasi , komitmen organisasi  proved as a mediating variable.